Analysis of Changes in Village Community Social Behavior after the Internet and Technological Advances - Candra Bakti Pramana; Maya Lumbangaol (IHSA Institute, 2024)
This study examines the impact of the internet and technological advances on village community social behavior. Using a mixed-methods approach, the research explores changes in social behavior within village communities following the integration of technology. The study employs theoretical frameworks such as Social Capital Theory and Diffusion of Innovations Theory to guide the analysis. Findings suggest that technology has led to increased connectivity and stronger social bonds among community members. However, it has also raised concerns about the negative impact on mental health and well-being, inequalities in technology access, and cultural shifts within village communities. The study highlights the need for a nuanced approach to technology integration, one that balances the benefits of technology with the preservation of traditional values and identities. By addressing these challenges, village communities can harness the transformative potential of technology to enhance social cohesion, economic prosperity, and cultural vitality.